Status and trends in international trade and local utilization of wildlife in Central America - Barborak, J.R; Morales, R; MacFarland, C; Swift, B; CATIE - Centro Agronómico Tropical de Investigación y Enseñanza (Centro Agronómico Tropical de Investigación y Enseñanza, Turrialba, Costa Rica, 2022)
Incluye 31 referencias bibliográficas